2007
DOI: 10.1007/bf02872669
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the social and physical contexts of physical activity across adolescence using ecological momentary assessment

Abstract: e.EMA showed that the social and physical contexts of adolescent exercise and walking vary as a function of gender, grade in school, day of the week, and season. Understanding the contexts of physical activity during the high school years can be helpful in designing interventions during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 42 publications
6
111
3
Order By: Relevance
“…The activities considered as 'job' activities were a mixture of both paid (eg, paper-round) and unpaid (eg, Boy Scouts) activities, which might be conducted either indoors or outdoors. A positive association between the time spent outdoors and increased physical activity has previously been suggested 32 and our results are in agreement with this. A key and consistent finding in this study is that the more active boys reported playing more sport.…”
Section: Comparison With Other Studiessupporting
confidence: 94%
“…The activities considered as 'job' activities were a mixture of both paid (eg, paper-round) and unpaid (eg, Boy Scouts) activities, which might be conducted either indoors or outdoors. A positive association between the time spent outdoors and increased physical activity has previously been suggested 32 and our results are in agreement with this. A key and consistent finding in this study is that the more active boys reported playing more sport.…”
Section: Comparison With Other Studiessupporting
confidence: 94%
“…London children aged 11-12 years reported that sedentary activities became more common in cold weather (Brodersen et al 2005). Dunton et al (2007) made electronically prompted diary recordings every 30 min for 4 days on 502 Californian students in Grades 9-12; deliberate exercise and walking were again recorded more frequently in the fall and spring than during the winter. Some of the objective data are for spring and fall rather than summer and winter; thus, Goran et al (1998) used doubly labelled water and gas consumption measurements to demonstrate that the active energy expenditures of 7-to 8-year-old children in Vermont and Alabama were 0.21-0.42 MJ/day greater in the spring than in the fall (ns).…”
Section: Childrenmentioning
confidence: 99%
“…While the articles to date have provided some evidence for the feasibility of collecting behavioral parameters from adolescents over a short period of time [8], the methodology commonly lacks physiological measurement and is limited to examining variables for a short duration (i.e., 4 days) [4]. The development of dynamical regulatory systems models will require long assessment windows or frequent repeated assessments; comprehensive assessment of behavioral, physiological, and subjective variables; and participants who are willing to comply with the methods necessary to develop intensive longitudinal data.…”
mentioning
confidence: 99%